2008
DOI: 10.1097/adm.0b013e31816c60c1
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Substance Abuse and Sexual Risks with Self-Reported Depressive Symptoms in Young Adults in Northern Thailand

Abstract: Depression among young adults is a significant mental health issue worldwide. Withdrawal from amphetamine and chronic alcohol use is associated with significant increases in depressive symptoms. Young adults with depressive symptoms are more likely to engage in sexual risk behaviors than peers who are not depressed. We investigated the association between substance abuse and sexual risk behaviors with recent depressive symptoms (using the Centers for Epidemiologic Studies Depression Scale [CES-D] scale) in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…The study showed that ATS users with high dose of drug use, which was related with higher frequency of drug use, have high risk of depression. The familiar finding was observed in a Thailand study that indicated frequent methamphetamine use was associated with depressive symptoms [14]. This study indicated that ATS users of cessation 12 month or longer period had significantly less risk of depressive symptoms than participants who continued to use ATS and a similar finding was observed from a prospective cohort study [8].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The study showed that ATS users with high dose of drug use, which was related with higher frequency of drug use, have high risk of depression. The familiar finding was observed in a Thailand study that indicated frequent methamphetamine use was associated with depressive symptoms [14]. This study indicated that ATS users of cessation 12 month or longer period had significantly less risk of depressive symptoms than participants who continued to use ATS and a similar finding was observed from a prospective cohort study [8].…”
Section: Discussionsupporting
confidence: 80%
“…Some studies showed that the patients seeking treatment for ATS dependence are more likely to be diagnosed with depression [12]. The factors related drug use were reported to be associated with depression, such as early onset ATS use (initiation use at 15 years or younger), the administration of injection and more frequent (≥4 days per week) ATS use [7], [13], [14]. Depression have controversial association with cessation of ATS use, a study indicated that depression is a major component of the withdrawal syndrome of ATS use during the first 3 weeks of abstinence [15], however an prospective cohort study found that depressive symptoms decreased significantly among those who stopped using ATS over the 12-month study period [8].…”
Section: Introductionmentioning
confidence: 99%
“…Between April 2005 and June 2006, 1263 young adults aged 18–25 years were screened, of whom 1189 were eligible (94%) and 983 (78%) were randomized (415 index participants and 568 members of their drug and/or sexual networks). Recruitment procedures and eligibility criteria have been described in detail elsewhere (Celentano et al, 2008). Reasons for ineligibility and non- randomization were primarily related to the index participants’ inability to enroll one of their drug or sexual network members into the trial within the specified window of time.…”
Section: Methodsmentioning
confidence: 99%
“…No studies have yet explored this issue in an international environment outside of the clinical setting. Thailand has experienced an epidemic rise in MA use, particularly among adolescents and young adults (UNODC, 2004), and this group has been found to have a high burden of depressive symptoms(Celentano et al, 2008). We examined the temporal relationship between long-term pattern of MA use and depressive symptoms in the context of a randomized behavioral trial to reduce the harms associated with drug use among non-treatment-seeking young MA users in northern Thailand.…”
Section: Introductionmentioning
confidence: 99%
“…Besides increasing mortality and morbidity (WHO, ), drug use is associated with an increased risk of mental disorder (Anglin, Burke, Perrochet, Stamper, & Dawud‐Noursi, ; Grella & Lovinger, ; Han, Gfroerer, & Colliver, ; Sherman et al, ). The form of mental illness most commonly associated with (any form of) drug use is depression (Celentano et al, ; Ford et al, ; Latkin, Davey‐Rothwell, Yang, & Crawford, ; Lev‐Ran et al, ; Marshall, & Werb, ; Reissner et al, ; Rounsaville, ). Depression is one of the major contributors to the global burden of disease (Lev‐Ran et al, ; Moussavi et al, ; Ustün, Ayuso‐Mateos, Chatterji, Mathers, & Murray, ).…”
Section: Introductionmentioning
confidence: 99%